(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
Background: This study aims to analyse the impact of public relations strategies on the promotion of Vision 2030 initiatives. Public relations, including media relations, crisis communication, and stakeholder engagement, are essential tools for shaping public perception and supporting national development plans. Method: A quantitative research approach is adopted for the study while the data collection technique employed is the structured questionnaires administered on a sample of 100 respondents. Descriptive analysis and correlation is done using statistical software known as SPSS in ascertaining the relationship between the proposed public relation strategies and the perception of Vision 2030 among the public. Findings: The study affirmed that management’s strategies of public relation have positively impacted public awareness and support to Vision 2030. Media relations and social media management enhance public communication. The stakeholders’ engagement is central to Vision 2030 goals promotion and success achievement. Recommendations: Media and social media strategies should be enhanced with the material of which the content is oriented in accordance with the designated demographic segment. Frequent and regular communication to the stakeholders would ensure that the news about the new Vision 2030 initiatives spreads widely hence getting support from many people. Moreover, the enhancement of crisis communication plans and protocols contributes to the increase in the public’s confidence and backing especially in turbulent times.